Palliative Care: Taking the Long View - García-Baquero Merino, María Teresa (Frontiers in Pharmacology, 2018)
Our medicalised modern cultures render reason and mystery mutually exclusive, define death by disease as failure, and dying as disgraceful. Providers and policymakers alike marginalise ageing and dying individuals, formulating largely ineffective strategies without palliative care and pain relief budgets. The aim of palliative care is to support the person with incurable illness to live their remaining life as well and as meaningfully as possible and to support them as they eventually die from their illness and reaching the natural end of their lives It acknowledges that each life is morally significant, restoring patients’ and families’ quality of life where possible, and attending meticulously to the dying period as necessary. Hospices are far more than mere buildings; they house an ethos of care. The field is currently challenged by its variable situation over the world and the pressing need to incorporate new technology to its practice. This article provides a review of some important milestones in the history and development of Palliative Care and evolution of Palliative Medicine in some countries, some current issues concerning consistency in its implementation, and some likely prospects for its future advance and expected expansion, from the perspective of one central question: “What constitutes the ethos of Palliative Care replicating its foundational philosophy and principles?” which helps to set the scene for possible future advances to integrate ethical, legal and social implications. Technology will help expansion by facilitating communication and acurately predicting needs.